Hukum Adat di Era Digital: Pendekatan Mediasi Virtual dalam Penyelesaian Sengketa Tradisional - Absi, Warmiyana Zairi; Haryadi, Tobi; Azmy, Rahmad Dani; Alhakim, Muhammad Dzikri (Lex Stricta : Jurnal Ilmu Hukum, 2025)
The advancement of digital technology has significantly transformed various aspects of life, including dispute resolution mechanisms. This article examines the application of virtual mediation as an alternative to traditional dispute resolution within the context of Indonesian customary law. Using a normative juridical method with conceptual and statutory approaches, the study finds that virtual mediation can serve as an effective, efficient, and adaptive solution for customary communities in the digital era, provided it upholds local wisdom and established customary procedures. However, challenges such as limited technological access, data security, and legal legitimacy must be addressed to ensure that virtual mediation is optimally implemented and aligned with the principles of customary law.